Recovery of atrioventricular conduction in patients with heart block after transcatheter aortic valve replacement. (4th August 2017) - Raelson, Colin A.; Gabriels, James; Ruan, Jonathan; Ip, James E.; Thomas, George; Liu, Christopher F.; Cheung, Jim W.; Lerman, Bruce B.; Patel, Apoor; Markowitz, Steven M.
Abstract: Introduction: Recovery of conduction has been demonstrated in >50% of patients who receive pacemakers (PPMs) for high‐degree atrioventricular block (HD‐AVB) after transcatheter aortic valve replacement (TAVR). Little information is available about the time course of conduction recovery in these patients and if any features predict early recovery of conduction. Methods: A retrospective review was performed of patients who underwent TAVR with balloon and self‐expanding valves who required PPMs for HD‐AVB. Serial PPM interrogations were analyzed to detect recovery of AV conduction. Analysis was performed to identify predictors and timing of conduction recovery. Results: Of a total population of 578 patients, 54 (9%) received PPMs for HD‐AVB. In multivariate analysis, predictors of HD‐AVB requiring a PPM included age (P = 0.014), right bundle branch block (OR 7.33 [3.64–14.8], P < 0.0001), atrial fibrillation (OR 2.16 [1.16–4.05], P = 0.016), and self‐expanding valves (OR 4.19 [2.20–7.97], P < 0.0001). Of the 54 patients who received PPMs, 38 had follow‐up sufficient to evaluate AV conduction recovery. Of these, 23 (61%) showed recovery of AV nodal conduction; 20 had already recovered by their first interrogation, a median of 22 days (IQR 14–31) post‐PPM placement. There were no statistically significant predictors of AV nodal conduction recovery, including type of valve implanted. Conclusions: A majority of patients who receive PPMs for HD‐AVB after TAVR recover AV conduction during followup, and in most patients conduction recovery occurs within weeks. These findings imply that programming to minimize ventricular pacing may be beneficial in a majority of these patients.